Hand hygiene practices in a neonatal intensive care unit in Ghana - Amgbo Asare; Christabel C. Enweronu-Laryea; Mercy J. Newman (Journal of Infection in Developing Countries)
Background: Compliance with hand hygiene recommendations is the most important measure in preventing health care-associated infections. The objective of this study was to assess the nature of patient contact and the hand hygiene practices of nurses and physicians in the neonatal intensive care unit in a tertiary hospital in Ghana. Methodology: Unobtrusive observation of patient contact, hand hygiene practices, and hand washing technique among nurses and physicians attending randomly selected newborns for five hours daily for two weeks. Patient contact categorized as low-risk or high-risk. Hand hygiene practice before and after patient contact categorized as clean uncontaminated, clean recontaminated, new gloves, unchanged gloves. Compliance to alcohol rub use assessed. Results: The patient to nurse/physician ratio varied from 9:1 to 12:1. There were 97 patient contacts of which 49 were high-risk and 48 low-risk. Most (73%) patient contacts were from nurses. Compliance to hand hygiene recommendations before versus after patient contact was 15.4% versus 38.5% for physicians and 14.1% versus 9.9% for nurses. Gloves were used for 60.8% patient contacts (85.7% high-risk, 35.4% low-risk); however, compliance to recommended procedure occurred in only 12.2% of high-risk contacts and none of the low-risk contacts. Gloves were not changed between patients in 43.7% of high-risk contacts and 88.2% of low-risk contacts. Hand washing protocol was generally followed. Alcohol hand rub was always available but was not used for hand hygiene. Conclusions: Hand hygiene compliance of physicians and nurses was low. Gloves and alcohol rub were not used according to recommended guidelines. Incorporating effective education programs that improve adherence to hand hygiene guidelines into the continuing education curriculum of health professionals is recommended.